Deregulasi Di Indonesia Perkembangan dan Dampaknya Terhadap Perbankan - Hidayat Wiweko, Nuryasman MN, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2001)
Deregulation packages are developed by government with the aims to enhance the development of the banking system and the national economy. This deregulation has a certain impact on the development of the banking system, i.e on the amount of banks and bank offices, the quantity of funds gathered from the society and credits given, which forms the positive side of deregulation. But on the other side, deregulation also has it’s negative side which should be taken in consideration to face the existing challenges and in order to be able to compete with other banks in the globalization era.